(untitled) (Global Journal of Management and Business Research, 2017)
The purpose of this article is to expose the necessity for large national private business organizations in the Republic of Honduras. A comparison was made with the early industrialized nations of the United Kingdom and the United States whose economies necessitated large private enterprises in order to attract large investments and professional management. It was proposed in the article that the government of Honduras selectively privatizes its large enterprises that are not essential to the defense and security of the country and are not natural monopolies. It was also suggested that the government needs to encourage and support the formation of new large private enterprises in order to create a competitive economy on a national, regional and global basis.